La tenencia de tierra y su impacto en los ingresos de los agricultores ecuatorianos en el año 2022. - Becerra Rojas, John Jairo (2025)
The high concentration of land in Ecuador, a legacy of agroexport models, limits the income of small farmers. Consequently, the overall objective is to evaluate this relationship using a statistical and econometric approach to formulate policy recommendations that can increase farm incomes. Data from the Ministry of Agriculture, Food and Rural Affairs and SIPA were used. The methodology included ordinary least squares regression analysis. Among the main findings, it was found that land tenure, level of education, use of irrigation have a significant impact on farm income. Secure land tenure allows farmers to invest more in their land, improving productivity and income. Technical training and education levels translate into better farming practices and more efficient use of resources. The use of irrigation also reflects its importance in increasing agricultural yields. Therefore, it is recommended to implement land redistribution policies and technical training programs for farmers, supported by the government to facilitate access to agricultural inputs. These measures could increase agricultural productivity and incomes, thereby reducing rural poverty and improving food security in Ecuador.